A Model-Driven Approach to Assessing the Fouling Mechanism in the Crossflow Filtration of Laccase Extract from Pleurotus ostreatus 202 - Páez, María Augusta (2025)
The primary application of membrane technology is the separation and purification of biotechnological products, with proteins and enzymes being integral components of these processes. Fouling of membranes during crossflow filtration is a prominent challenge. This work aims to evaluate filtration performance and fouling, particularly related to pore-blocking mechanisms, throughout one crossflow microfiltration (MF) and six consecutive ultrafiltration (UF) stages implemented for laccase extracts produced by Pleurotus ostreatus 202 fungi. Activity concentration factor, recovery efficiency and purification factor are the key performance criteria. To assess membrane fouling, dead-end filtration models formulated in 1982 were compared to crossflow filtration models developed in 2011. The experimental flux decline in all filtration stages is satisfactorily described by crossflow models accounting for removal term during pore-blocking, so R2 is an appropriate fitting parameter.Complete pore blocking mechanism significantly impacts the MF, UF 1000, UF 100 and UF 10 stages, with the highest filtration constant (KbF) estimated at 12.60×10-4 (s-1). Conventional standard pore blocking is evident in all filtration stages, but the lowest impact on fouling is observed since the progressive flux decline. Although intermediate pore blocking mechanism appears in all filtration stages, UF 100 is the most affected, with a filtration constant (KiF) of 16.70 (m-1). This tendency is confirmed by the highest purification factor (6.95) and the 65, 62 and 56 kDa laccasses found in the retentate. Finally, the absence of cake formation and the permeate volume recovered indicates that neither membrane was exposed to exhaustive fouling that could not be reversed by backwashing.